Dynamic Cerebral Autoregulation in Embolic Stroke of Undetermined Source - Ma, Hongyin; Liu, Jia; Lv, Shan; Zhang, Peng; Guo, Wei-Tong; Qu, Yang; Guo, Zhen-Ni; Yang, Yi (Frontiers in Physiology, 2020)
Background and Purpose: Dynamic cerebral autoregulation (dCA) in acute ischemic stroke is probably compromised. Although the characteristics of dCA in different types of stroke have been largely investigated, dCA in embolic stroke of undetermined source (ESUS) remains poorly understood. In this group, we aimed to elucidate the characteristics of dCA and their relevance to clinical outcomes. Methods: The study enrolled 77 ESUS patients and 50 controls. Bilateral cerebral blood flow velocities (CBFV) of middle cerebral arteries and arterial blood pressure were simultaneously recorded using a transcranial Doppler combined with a servo-controlled finger plethysmograph. Transfer function analysis was used to obtain dCA parameters including phase, gain, coherence at very low frequency (VLF) and low frequency (LF), and the rate of recovery (RoRc) of CBFV. A multivariable logistic regression model was established to explore the relationship between dCA and clinical outcomes. Results: Gain at VLF and LF, phase at LF, and RoRc of CBFV in bilateral hemispheres of the ESUS group were consistently worse than those of the control group (all P<0.001). Bilateral RoRc of CBFV was significantly higher in patients with favorable outcomes than in those with unfavorable outcomes (stroke hemisphere: P<0.001; non-stroke hemisphere, P=0.029). RoRc of CBFV in stroke hemisphere >13.3%/s was an independent predictor of favorable clinical outcomes (adjusted odds ratio=24.66, 95% CI: 4.72–128.95, P<0.001). Conclusions: dCA was relatively impaired in both stroke and non-stroke hemispheres in ESUS patients, and functioning dCA after ESUS may indicate favorable clinical outcomes.